2003
DOI: 10.1016/s0378-1097(03)00598-6
|View full text |Cite
|
Sign up to set email alerts
|

Phylogenetic affinity of aGiardia lambliacysteine desulfurase conforms to canonical pattern of mitochondrial ancestry

Abstract: Among a few potential archezoan groups, only the Metamonada (diplomonads, retortamonads, and oxymonads) still retain the status of amitochondriate protists that diverged before the acquisition or retention of mitochondria. Indeed, finding that diplomonad genomes harbor a gene encoding a mitochondrial type chaperonin 60, the most compelling evidence for their secondarily amitochondriate nature, may be interpreted as an acquisition of this important general chaperone during some transient K-proteobacterial endos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
22
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 40 publications
1
22
0
Order By: Relevance
“…Detection of two genes in T. vaginalis coding for IscS homologs with putative hydrogenosomal import signals suggested that FeS-center assembly in hydrogenosomes might be homologous to the mitochondrial system (24). The clustering of the derived amino acid sequences with mitochondrial homologs in phylogenetic reconstructions strengthened this notion further (24,25). Here, we show that one of these genes (tviscS-2) is expressed, translocated to hydrogenosomes, and involved in the biosynthesis of FeS proteins.…”
supporting
confidence: 56%
See 2 more Smart Citations
“…Detection of two genes in T. vaginalis coding for IscS homologs with putative hydrogenosomal import signals suggested that FeS-center assembly in hydrogenosomes might be homologous to the mitochondrial system (24). The clustering of the derived amino acid sequences with mitochondrial homologs in phylogenetic reconstructions strengthened this notion further (24,25). Here, we show that one of these genes (tviscS-2) is expressed, translocated to hydrogenosomes, and involved in the biosynthesis of FeS proteins.…”
supporting
confidence: 56%
“…Although the data are scanty, the answer is probably yes. In all of the amitochondriate organisms studied so far, a gene encoding an IscS homolog has been recognized and found to be part of the clade formed by typical mitochondrial homologs (24,25,43). It should be stressed that the studied amitochondriate groups belong to separate taxonomic lineages.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Key proteins in this pathway; cysteine desulphurase (IscS) and scaffolding protein (IscU), appear to have originated from the mitochondrial endosymbiont (Tachezy et al 2001;Emelyanov 2003;van der Giezen et al 2004). The maturation and export of Fe/S clusters has been suggested as a possible common function of all mitochondrial homologues (Tachezy et al 2001;Embley et al 2003a).…”
Section: Conclusion Speculations and Outlookmentioning
confidence: 99%
“…In eukaryotes, this process takes place exclusively in double membrane-bound organelles including mitochondria (11), hydrogenosomes (12), and chloroplasts (13). Phylogenetic analyses placed the Giardia IscS (GiiscS) within the mitochondrion͞ hydrogenosome clade (10,14). In addition, GiiscS and Giardia scaffold protein (GiiscU) colocalized inside vesicles surrounded by a double membrane and high-speed cellular fractions of Giardia catalyzed reconstitution of FeS clusters in an apoprotein lacking FeS moieties (4).…”
mentioning
confidence: 99%